Video-assisted thoracic surgery for esophagectomy: evolution and prosperity - Guo, Wei; Xiang, Jie; Yang, Su; Li, Hecheng (Video-Assisted Thoracic Surgery, 2017)
Esophageal cancer is the eighth most commonly diagnosed cancer worldwide and the sixth most common cause of cancer-related death. For esophageal cancer patients without contraindications, esophagectomy remains the vital remedy despite great achievement of adjuvant therapy and neoadjuvant therapy. However, esophagectomy involves two or three compartment dissection, leading to high morbidity and mortality as well as profound decrease in quality of life. Since Dr. Franz Torek successfully conducted the first transthoracic esophagectomy in 1913, various surgical approaches have been established to resect the esophagus and reconstruct the alimentary canal. Facing with the huge trauma caused by traditional open esophagectomy, thoracic surgeons have been making every effort to make esophagectomy minimally invasive. Among these attempts, the emergence and improvement of video-assisted thoracic surgery is the milestone event. Nowadays video-assisted esophagectomy has been performed worldwide and proved to induce less surgical trauma with uncompromised efficiency. This is a review of the pertinent literature regarding this technique.